Aktivitas Masyarakat di Desa Lambanan pada Zona Tradisional Taman Nasional Gandang Dewata (TNGD) - Utami A, Widyanti (Pangale Journal of Forestry and Environment, 2022)
Gandang Dewata National Park (TNGD) is a national park that was established in 2016, before being designated as a national park the community had lived in the Gandang Dewata National Park area. Communities depend on the forest for their lives, such as the use of wood and non-timber forest products. This study aims to identify the types of community activities in the customary area of Gandang Dewata National Park. This research was conducted from October to November 2022 in the traditional area of Lambanan Village, Gandang Dewata National Park. The data collection method used is the Rapid Rural Appraisal method. Data were analyzed by descriptive qualitative data. The results showed that there were seven activities carried out by the community in the traditional area of Lambanan Village TNGD as a form of livelihood and as fulfilling household needs. Activities carried oyt by the community include making use of springs, collection firewood, collecting vegetables, gardening, tapping resin, collecting wild honey and hunting.